Searching for the role of protein phosphatases in eukaryotic microorganisms - da-Silva,A.M. (1999)
Preference for specific protein substrates together with differential sensitivity to activators and inhibitors has allowed classification of serine/threonine protein phosphatases (PPs) into four major types designated types 1, 2A, 2B and 2C (PP1, PP2A, PP2B and PP2C, respectively). Comparison of sequences within their catalytic domains has indicated that PP1, PP2A and PP2B are members of the same gene family named PPP. On the other hand, the type 2C enzyme does not share sequence homology with the PPP members and thus represents another gene family, known as PPM. In this report we briefly summarize some of our studies about the role of serine/threonine phosphatases in growth and differentiation of three different eukaryotic models: Blastocladiella emersonii, Neurospora crassa and Dictyostelium discoideum. Our observations suggest that PP2C is the major phosphatase responsible for dephosphorylation of amidotransferase, an enzyme that controls cell wall synthesis during Blastocladiella emersonii zoospore germination. We also report the existence of a novel acid- and thermo-stable protein purified from Neurospora crassa mycelia, which specifically inhibits the PP1 activity of this fungus and mammals. Finally, we comment on our recent results demonstrating that Dictyostelium discoideum expresses a gene that codes for PP1, although this activity has never been demonstrated biochemically in this organism.